Improving Teachers’ Digital Pedagogical Competence through Action Research-Based Technology Integration - Pratama, Yudhistira Anugerah; Audina Margaretha Putri; Isabelle van den Berg (Indonesian Journal of Action Research, 2025)
Purpose – This study investigated how action research-based technology integration improves teachers' digital pedagogical competence across multiple dimensions, examining the mechanisms and contextual factors that facilitate this development. Design/methods – Employing a convergent parallel mixed-methods design, this year-long study involved 24 secondary school teachers organized into four collaborative action research teams. Quantitative data were collected through pre-test and post-test TPACK surveys and DigCompEdu self-assessments at three time points, analyzed using paired-samples t-tests. Qualitative data included reflective journals, meeting transcripts, focus group interviews, and classroom observations, analyzed through thematic analysis. Findings– Results revealed statistically significant improvements across all seven TPACK domains (p <.001), with largest effect sizes in integrated knowledge areas; TPACK (d = 1.72), TPK (d = 1.60), and TCK (d = 1.48). By study's end, 58.3% of teachers reached leader level in professional engagement, and 45.8% in teaching & learning competence. Four mechanisms facilitated development; systematic experimentation, evidence-based reflection, collaborative problem-solving, and iterative refinement, with leadership support and team dynamics emerging as critical contextual enablers. Keyword: Digital Pedagogical Competence, Action Research, Technology Integration, TPACK, Teacher Professional Development